Third-party effects of arbitral awards: res judicata against privies, non-mutual preclusion and factual effects - Pika, Maximilian (International arbitration law library, 2019)
The Contractual Perception of Arbitral Jurisdiction as Trigger of Multi-Fora Disputes --A Proceduralist Connotation of Arbitral Res Judicata under National Laws --Judgments’ Third-Party Effects as a Shift of the Participatory Burden --Third-Party Effects of Arbitral Awards under National Arbitration Laws --Third-Party Effects of Arbitral Awards under the New York Convention --Third-Party Effects of Arbitral Awards in Private International Law --The Unshaped Factual Effect of Arbitral Awards --Transnational Res Judicata and Third-Party Effects Before Arbitral Tribunals --The Application of Res Judicata Principles to Jurisdictional Decisions --Conclusions.
Keywords: Hochschulschrift; Internationale Schiedsgerichtsbarkeit; Handelsschiedsgerichtsbarkeit; Dritter; Schiedsspruch